2014
DOI: 10.4103/2152-7806.140191
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer′s disease: The role for neurosurgery

Abstract: Dementia, most commonly caused by Alzheimer's disease (AD), affects approximately 35 million people worldwide, with the incidence expected to increase as the population ages. After decades of investigation, AD is now understood to be a complex disease that affects behavior and cognition through several mechanisms: Disrupted neuronal communication, abnormal regional tissue metabolism, and impaired cellular repair. Existing therapies have demonstrated limited efficacy, which has spurred the search for specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Several animal studies have shown that delivery of nerve growth factor (NFG) -a member of neurotrophin family that plays a role in cholinergic synaptic remodeling in the adult CNS-in basal forebrain (anterior part of the brain, cerebral hemispheres, thalamus and hypothalamus) by encapsulated cell biodelivery (ECB) could arrest or even reverse the neuronal degeneration process [31,32]. In 2012 Wahlberg et al, evaluated the safety and the clinical efficacy of ECB for use in humans [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several animal studies have shown that delivery of nerve growth factor (NFG) -a member of neurotrophin family that plays a role in cholinergic synaptic remodeling in the adult CNS-in basal forebrain (anterior part of the brain, cerebral hemispheres, thalamus and hypothalamus) by encapsulated cell biodelivery (ECB) could arrest or even reverse the neuronal degeneration process [31,32]. In 2012 Wahlberg et al, evaluated the safety and the clinical efficacy of ECB for use in humans [32].…”
Section: Discussionmentioning
confidence: 99%
“…These molecular alterations lead to neuronal loss and cerebral atrophy in different regions of the brain involving frontal, temporal, parietal, hippocampus and entorhinal cortex (EC). AD also disrupts the neuronal connections between the cortical and subcortical areas [4,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AD presents a difficult medical problem across many clinical disciplines including neurology and gerontology (Willhite et al, 2014). Its pathological changes primarily consist of brain tissue atrophy with a large amount of β-amyloid peptide (Aβ) deposition in the brain tissue and brain blood vessels, and the presence of senile plaques and neurofibrillary tangles in hippocampal neurons (Pereira et al, 2014) Studies have shown that multiple factors including the destruction of calcium homeostasis, apolipoprotein E, free radical damage, metabolic disorders, and cholinergic injury might induce AD (Arevalo-Rodriguez et al, 2014;Bazin and Bratu, 2014;Savioz et al, 2014). However, the pathogenesis of AD has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…62 In AD there is decreased activity in the precuneus and posterior cingulate, which comprise the posterior default mode network, with decreased connectivity in all areas as the disease progresses. 83 …”
mentioning
confidence: 99%